Boosting infrared energy transfer in 3D nanoporous gold antennas. Issue 2 (21st December 2016) - Garoli, D.; Calandrini, E.; Bozzola, A.; Ortolani, M.; Cattarin, S.; Barison, S.; Toma, A.; De Angelis, F.
Abstract : Demonstration of boosting infrared energy transfer in 3D nanoporous gold antennas. Abstract : The applications of plasmonics to energy transfer from free-space radiation to molecules are currently limited to the visible region of the electromagnetic spectrum due to the intrinsic optical properties of bulk noble metals that support strong electromagnetic field confinement only close to their plasma frequency in the visible/ultraviolet range. In this work, we show that nanoporous gold can be exploited as a plasmonic material for the mid-infrared region to obtain strong electromagnetic field confinement, co-localized with target molecules into the nanopores and resonant with their vibrational frequency. The effective optical response of the nanoporous metal enables the penetration of optical fields deep into the nanopores, where molecules can be loaded thus achieving a more efficient light–matter coupling if compared to bulk gold. In order to realize plasmonic resonators made of nanoporous gold, we develop a nanofabrication method based on polymeric templates for metal deposition and we obtain antenna arrays resonating at mid-infrared wavelengths selected by design. We then coat the antennas with a thin (3 nm) silica layer acting as the target dielectric layer for optical energy transfer. We study the strength of the light–matter coupling at the vibrational absorption frequency of silica at 1240 cm −1 through the analysis of the experimental Fano lineshape that is benchmarked against identical structures made of bulk gold. The boost in the optical energy transfer from free-space mid-infrared radiation to molecular vibrations in nanoporous 3D nanoantenna arrays can open new application routes for plasmon-enhanced physical–chemical reactions.